2019
DOI: 10.1002/oby.22650
|View full text |Cite
|
Sign up to set email alerts
|

Baseline Psychosocial and Demographic Factors Associated with Study Attrition and 12‐Month Weight Gain in the DIETFITS Trial

Abstract: Objective The purpose of this study was to examine correlates of failure—trial attrition and weight gain—in a randomized clinical weight‐loss trial. Methods The Diet Intervention Examining The Factors Interacting with Treatment Success (DIETFITS) trial included 609 adults (18‐50 years; BMI 28‐40). Participants were randomized to a 12‐month healthy low‐fat or healthy low‐carbohydrate diet for weight loss. At baseline, participants completed psychosocial, demographic, and anthropometric measures. Stepwise logist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 42 publications
1
33
0
Order By: Relevance
“…Together with the consideration of the aforementioned limitations, future studies could consider the following steps to provide additional understanding of FA impacts on children and adolescents. First, a recent study 52 found that the YFAS was the strongest predictor of poor response to weightloss treatment among adults; however, it is unclear whether the same results can be replicated among children. Notably, there is a dearth of research investigating how the YFAS‐C predicts treatment outcomes in children.…”
Section: Discussionmentioning
confidence: 99%
“…Together with the consideration of the aforementioned limitations, future studies could consider the following steps to provide additional understanding of FA impacts on children and adolescents. First, a recent study 52 found that the YFAS was the strongest predictor of poor response to weightloss treatment among adults; however, it is unclear whether the same results can be replicated among children. Notably, there is a dearth of research investigating how the YFAS‐C predicts treatment outcomes in children.…”
Section: Discussionmentioning
confidence: 99%
“…YFAS scores also appear to be clinically relevant. Although some studies have not found a link between YFAS scores and response to weight-loss treatments (80), a recent large-scale weight-loss treatment trial found that YFAS scores were the strongest psychosocial predictor of attrition and failure to lose weight (40). The literature is mixed regarding the predictive utility of presurgery YFAS scores for response to weight-loss surgery.…”
Section: Conceptualization and Assessment Of Food Addictionmentioning
confidence: 99%
“…In general, FA symptom severity is associated with higher BMI ( Pursey et al, 2014 ). Some studies report higher study attrition and lower effectiveness of WLPs in individuals experiencing FA, while other studies did not find differences to individuals who are not experiencing FA ( Burmeister et al, 2013 ; Clark and Saules, 2013 ; Meule et al, 2015 ; Fielding-Singh et al, 2019 ). Yet, the prevalence of FA in WLP samples is high (up to 34,5–38%; Meule et al, 2015 ; Vidmar et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%